THE LIFE FIGHTER: (A Success Story of Butonese Migrant Traders, Study in Rumah Tiga Village Market, Teluk Ambon District) - LUDWINA PORMES; FERDINAN ROCKY PARERA (CV KULTURA DIGITAL MEDIA, 2021)
This study aims to explain how migrant traders are able to develop their business and explain social relations among migrant traders so that immigrant traders of Butonese ethnicity are able to develop their business. and survive overseas, even more developed than local traders. This study will also explain what influences the success of immigrant traders overseas. The basic reason that prompted this research to be carried out is because there has been no in-depth study and research using social economic concepts about the phenomenon of migrant traders in the Rumah Tiga village market that has succeeded and developed overseas. This research was conducted using qualitative analysis using a phenomenological approach to explain the phenomenon of migrant traders in the Rumah Tiga village market and their ability to develop and succeed overseas. Based on the concept of thought that was built, it will describe in depth the indicators that determine the success of migrant traders overseas and scientifically this research will later become part of the learning process of local traders on the success of migrant traders in developing their business and succeeding.